Pan-cancer analysis of PIEZO1: a promising biomarker for diagnosis, prognosis, and targeted therapies - Wang, Qian; Yu, Yan; Liang, Xiao; Wan, Dan; Du, Ke; Zhu, Pengpeng (Frontiers in Immunology, 2025)
IntroductionPiezo-type mechanosensitive channel component 1 (PIEZO1), a mechanically gated cation channel involved in calcium signaling, has been recognized as a potential oncogene in some cancers. However, its comprehensive pan-cancer role remains unexplored.MethodsThis study used The Cancer Genome Atlas (TCGA) data to analyze PIEZO1 expression profiles. Diagnostic value was evaluated using Receiver Operating Characteristic (ROC) curve analysis, with primary tumor samples as cases and adjacent normal tissues as controls. Prognostic value was determined through Cox regression and Kaplan-Meier survival analyses. Clinical correlations were detected using non-parametric tests and logistic regression. Genomic alterations were identified via the cBioPortal database. Functional pathways were analyzed using the R language. The association between PIEZO1 and tumor microenvironment scores (Stromal, Immune, ESTIMATE) or immune checkpoint markers (CD274, CTLA4, LAG3, PDCD1, PDCD1LG2) were analyzed using the R language. Quantitative Real-Time PCR (qRT-PCR) and Western Blotting (WB) were performed to quantify PIEZO1 expression in clinical specimens. Colony formation and wound healing assays assessed PIEZO1’s in vitro effects on cancer cells, while xenograft models evaluated its in vivo impact on tumor growth.ResultsOur analysis revealed that PIEZO1 has diagnostic and prognostic value across different cancer types. Elevated PIEZO1 expression was associated with advanced tumor grade and stage. Genomic alterations in PIEZO1 were found in 4% of pan-cancer patients. Functional enrichment analyses revealed that PIEZO1-coexpressed genes were significantly enriched in ECM-receptor signaling, cell migration, and ion homeostasis. PIEZO1 positively correlated with tumor microenvironment scores and immune checkpoints. Experimental validation confirmed PIEZO1 overexpression in LIHC and its pro-tumorigenic role in vitro/in vivo.ConclusionOur findings indicate that PIEZO1 is a promising marker for the diagnosis, prognosis, and development of targeted pan-cancer therapies.